Design and synthesis of new ultra-low band gap thiadiazoloquinoxaline-based polymers for near-infrared organic photovoltaic application. Issue 18 (4th February 2016) - Keshtov, M. L.; Kuklin, S. A.; Radychev, N. A.; Nikolaev, A. Yu.; Koukaras, E. N.; Sharma, Abhishek; Sharma, G. D.
Abstract : Two D–A copolymers, F1 andF2, with fluorene and thiazole units were substituted, respectively, on a thiadiazoloquinoxaline (TDQ) unit to enhance the electron-accepting strength of TDQ. Abstract : Two D–A copolymers, F1 andF2, with fluorene and thiazole units were substituted, respectively, on a thiadiazoloquinoxaline (TDQ) unit to enhance the electron-accepting strength of TDQ. The copolymers were synthesized by a cross-coupling Stille reaction and their optical and electrochemical properties were examined, which revealed that they have ultra-low band gaps and absorption in the near-infrared. These copolymers were employed as donors along with PC71 BM as an electron acceptor for the fabrication of solution-processed bulk heterojunction (BHJ) polymer solar cells. After the optimization of the donor-to-acceptor weight ratio and the solvent additive (4 v% DIO as solvent additive), devices withF1 :PC71 BM andF2 :PC71 BM displayed power conversion efficiencies (PCEs) of 5.80% and 3.32%, respectively. AlthoughF2 possesses a broader absorption profile compared withF1, the lower value of PCE for theF2 -based device was attributed to the low LUMO offset betweenF2 and PC71 BM, which limited the exciton dissociation. The abovementioned results indicate that these copolymers can be utilized for ternary BHJ and tandem solar cells to achieve a high PCE.